2016
DOI: 10.1200/jco.2015.66.0001
|View full text |Cite|
|
Sign up to set email alerts
|

Gain of 1q As a Prognostic Biomarker in Wilms Tumors (WTs) Treated With Preoperative Chemotherapy in the International Society of Paediatric Oncology (SIOP) WT 2001 Trial: A SIOP Renal Tumours Biology Consortium Study

Abstract: PurposeWilms tumor (WT) is the most common pediatric renal tumor. Treatment planning under International Society of Paediatric Oncology (SIOP) protocols is based on staging and histologic assessment of response to preoperative chemotherapy. Despite high overall survival (OS), many relapses occur in patients without specific risk factors, and many successfully treated patients are exposed to treatments with significant risks of late effects. To investigate whether molecular biomarkers could improve risk stratif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 112 publications
(91 citation statements)
references
References 30 publications
3
88
0
Order By: Relevance
“…Therefore, prognostic biomarkers may help to improve risk‐adapted therapy. We studied gains of 1q in GCT since this chromosomal aberration has been reported to be associated with unfavorable prognosis in other pediatric neoplasms such as Wilms tumors and brain tumors and is a known genetic alteration in Type I GCT. However, in our cohort of pediatric GCT, this alteration is not associated with inferior outcome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, prognostic biomarkers may help to improve risk‐adapted therapy. We studied gains of 1q in GCT since this chromosomal aberration has been reported to be associated with unfavorable prognosis in other pediatric neoplasms such as Wilms tumors and brain tumors and is a known genetic alteration in Type I GCT. However, in our cohort of pediatric GCT, this alteration is not associated with inferior outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Gains of 12p have recently also been detected in prepubertal testicular teratomas, which represent Type I GCT in children . Furthermore, gain of chromosome 1q, which is known to be associated with poor prognosis in a variety of malignancies of the childhood (eg, Wilms tumor or pediatric brain tumors), was examined for its prognostic relevance in pediatric GCT …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15] Prognostic features include stage, tumor weight, histology at baseline and following preoperative chemotherapy, 16 and genetic markers such as 1q gain and loss of heterozygosity at 1p and 16q. 17,18 The most common sites of metastasis in patients with stage IV WT are the lung followed by the liver. 13,16,19 Other sites are rare, but bone and brain have been reported more often at relapse rather than at primary diagnosis.…”
Section: Large Clinical Trial Groups Such As Nwts Group Internationalmentioning
confidence: 99%
“…The most recent series of unilateral WT studies have just been completed and the 4 year EFS and OS outcomes are shown in Table 2 .SIOP protocol uses stage and histological risk group assigned by assessment of the tumour's response to neoadjuvant chemotherapy to stratify patients but the recent emergence of 1q gain as a new biomarker of recurrence risk is likely to change the future consideration of biomarkers in the determination of subsequent therapeutic regimens . 45,46 Before considering 1q gain for clinical use, the heterogeneity of its expression within the tumor needs to be fully assessed and its prognostic significance needs to be validated in an independent sample set. 47 Recently, several new Wilms tumour genes have been discovered .…”
Section: Risk Stratification and Overall Oncological Therapywho Gets mentioning
confidence: 99%